Risk Indicators for Urinary Tract Infections in Low Risk Pregnancy and the Subsequent Risk of Preterm Birth - Dominique E. Werter; Brenda M. Kazemier; Caroline Schneeberger; Ben W. J. Mol; Christianne J. M. de Groot; Suzanne E. Geerlings; Eva Pajkrt (MDPI AG, 2021)
Symptomatic urinary tract infections are associated with preterm birth. However, data on risk indicators for urinary tract infections are limited and outdated. The research is a secondary analysis. The study was a prospective multicenter cohort study of low-risk pregnant women. Logistic regression was used to identify risk indicators for urinary tract infections. The incidence of urinary tract infections was 9.4%. Multivariate logistic regression showed that a history of recurrent urinary tract infections and the presence of asymptomatic bacteriuria in the present pregnancy were associated with urinary tract infections (resp. OR 3.14, 95%CI 1.40-7.02 and OR 1.96 95%CI 1.27-3.03). Women with a urinary tract infection were at increased risk of preterm birth compared to women without a urinary tract infection (12 vs. 5.1%; adjusted HR 2.5 95%CI 1.8-3.5). This increased risk was not found in women with the identified risk indicators (resp. 5.3% vs. 5.1%, adjusted HR 0.35 95%CI 0.00-420 and adjusted HR 1.5 95CI% 0.59-3.9). In conclusion, in low-risk pregnant women, risk indicators for urinary tract infections are: a history of recurrent urinary tract infections and the presence of asymptomatic bacteriuria. The risk of preterm birth is increased in women with a urinary tract infection in this pregnancy. However, women with recurrent urinary tract infections and asymptomatic bacteriuria this pregnancy appear not to be at increased risk of preterm birth.